Endomyocardial biopsy: what future in arrhythmogenic right ventricular dysplasia diagnosis?. (25th November 2020) - Maragna, R; Trombara, F; Frappampina, A; Dello Russo, A; Gasperetti, A; Catto, V; Conte, E; Vettor, G; Sicuso, R; Sommariva, E; Natale, A; Andreini, D; et al.
Abstract: Background: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a leading cause of sudden cardiac death, but its diagnosis is challenging and the role of endomyocardial biopsy (EMB) is controversial and has been recently questioned. Purpose: We aimed to 1) analyse the role of EMB in improving the diagnostic performance of 2010 Task Force Criteria (TFC) in the diagnosis of ARVC; 2) assess EMB safety in our population. Methods: We retrospectively analysed data from 54 consecutive patients admitted to our Hospital with a clinical suspicion of ARVC undergoing endomyocardial biopsy. During hospitalization a complete assessment was performed for every patient (including electrocardiogram, echocardiogram, cardiac MRI, genetic analysis, and electroanatomic-mapping-guided endomyocardial biopsy). ARVC diagnosis was assessed for every patient using both traditional 2010 TFC and a non-invasive modified TFC (2010 TFC criteria excluding biopsy). Results: Overall, 9/54 (17%) patients showed a left-dominant variant of ARVC and were therefore excluded from the analysis. Non-invasive modified TFC allowed 16/45 (36%) patients to receive a definite diagnosis; when biopsy results were added the number of definite diagnosis increased to 22/45 (49%), increasing the number of patients with a definite diagnosis by 13%. More specifically: 8/11 patients not reaching a possible diagnosis were reclassified as either possible (4/8) or borderline (4/8); 3/9 patients with a possible diagnosis were reclassified as borderline; 6/9 borderline patients received a definite diagnosis of ARVC. Globally, in 6 out of 29 patients with a non-definite diagnosis, EMB confirmed ARVC diagnosis and 17/45 (38%) patients received an upgrade in their diagnostic status with EMB. Notably, EMB also revealed the coexistence of myocarditis and fibro-fatty replacement in 5/45 (9%) patients. No patient experienced complications related to EMB. Conclusions: Endomyocardial biopsy is a safe, reliable, and useful tool for ARVC diagnosis, allowing to upgrade the diagnostic status of 38% of our patients with a suspect of ARVC diagnosis. It should be performed in experienced centers and it should be guided by electro-anatomic mapping, to maximize its diagnostic power. Funding Acknowledgement: Type of funding source: None